Strengthening of Civic Disposition through Cooperative Learning Methods - Firsty Mariana; Ana Andriani (UM Purwokerto Press, 2025)
This study aims to: (1) describe the implementation of cooperative learning in strengthening students' civic dispositions at SD Negeri Menganti 04 Kesugihan, Cilacap; (2) identify key aspects of cooperative learning that foster responsibility, collaboration, and mutual respect; and (3) examine how this method encourages active participation and increases students’ awareness of civic values in everyday life. Using a descriptive qualitative approach, the study involved 29 sixth-grade students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed thematically. The results reveal that cooperative learning was implemented through structured group tasks, clear role division, and reflective discussions that promoted inclusive participation. These elements effectively nurtured students' civic dispositions by encouraging them to collaborate, respect differing opinions, and engage meaningfully in group work. The most influential aspects were the structured activities and clear task expectations that required every student to contribute. Furthermore, cooperative learning significantly enhanced students’ civic awareness—particularly in terms of responsibility, discipline, empathy, and social engagement. This study provides insights into the potential of cooperative learning as a powerful method for character and civic education at the elementary level.